A review of the concept and measures of audit quality across three decades of research - Menezes Montenegro, Tânia (2018)
This study provides a comprehensive literature review of audit quality and it explores three decades of audit research (1980 to 2010). The DeFond and Zhang (2014) framework is used to present and discuss several perspectives on the concept and measures of audit quality, its inherent limitations and main strengths, adding a United States of America (U.S.) versus international studies comparative approach. The study is of interest to students, academic researchers, practitioners, standard setters/regulators and all those interested in understanding audit quality, from a U.S. versus international perspective.